2002
DOI: 10.1046/j.1365-3083.2002.01042.x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Lacrimal Gland Autoantigen in the NOD Mouse Model of Sjögren's Syndrome

Abstract: Recent research has demonstrated a crucial role for autoantibodies in the pathogenesis of Sjögren's syndrome (SS)‐like disease in the non‐obese diabetic (NOD) mouse, but it remains to be determined which antibody species among all those present are directly related to the various aspects of pathology. To identify autoantigens in the NOD mouse system, we have taken the approach of using immunoglobulin (Ig)G purified from sera of NOD mice exhibiting SS‐like symptoms to screen cDNA expression libraries derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In contrast to these strains, we found that the NOD.B10.H2 b strain spontaneously develops autoimmune lacrimal keratoconjunctivitis with age. Serum autoantibodies to acinar and ductal epithelial cells of exocrine glands, 52-kDa SS-A/Ro, M3R, 120-kDa α-foldrin and LPG10 have been previously detected in NOD mice [10,25]. Histopathologically, the autoimmune inflammation in the secretory glands of NOD mice accelerates acinar cell loss via apoptosis and necrosis and ductal epithelial hyperplasia by local production of cytotoxic auto-and paracrine factors [16,26].…”
Section: Discussionmentioning
confidence: 96%
“…In contrast to these strains, we found that the NOD.B10.H2 b strain spontaneously develops autoimmune lacrimal keratoconjunctivitis with age. Serum autoantibodies to acinar and ductal epithelial cells of exocrine glands, 52-kDa SS-A/Ro, M3R, 120-kDa α-foldrin and LPG10 have been previously detected in NOD mice [10,25]. Histopathologically, the autoimmune inflammation in the secretory glands of NOD mice accelerates acinar cell loss via apoptosis and necrosis and ductal epithelial hyperplasia by local production of cytotoxic auto-and paracrine factors [16,26].…”
Section: Discussionmentioning
confidence: 96%
“…An autoimmune mechanism links reduced lacrimal function and diabetes in the non‐obese diabetic (NOD) mouse (Moore and others 1996, van Blokland and Versnel 2002, Cha and others 2002). A lacrimal autoantibody has been detected in NOD mice but not in a control population and may be the link between the lacrimal exocrinopathy and the pancreatic endocrinopathy (Esch and others 2002). Other abnormalities in lacrimal and pancreatic islet apoptosis (Kong and others 1998, Silva and others 2003) and dendritic cell function (van Blokland and others 2000) link autoimmune destruction in different organs in both the NOD and MRL/lpr mouse models of lacrimal gland dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The genes responsible for effects in the nonobese diabetic mouse model of SS on mouse chromosome 1 [58•], 3 [59], and 4 [60] would become candidates when the genes are identified. Other findings in the nonobese diabetic mouse, such as the lysosomal membrane glycoprotein-10 autoantigen [61], high levels of matrix metalloproteases [62], and cysteine proteases [63], also suggest candidate genes.…”
Section: Other Candidate Genesmentioning
confidence: 99%